The relative influence of value priorities ethnicity and worries in the determination of political party affiliation amongst Ugandan university students - Kibanja, Grace M (Rhodes University, Faculty of Humanities, Department of Psychology, 1999)
This study examines the relative influence of value priorities, ethnicity and 'worries' in the determination of political party affiliation amongst Ugandan university students. Schwartz's values questionnaire was administered to 309 male and 176 female first year students from the faculties of engineering, medicine, law, commerce, social sciences, sciences, education and mass communication at Makerere University Uganda. The sample included respondents from all of the six sub-ethnic groups in Uganda. Respondents also covered the major religious groups in the country and were also representative of the major political parties. Results from the statistical analysis on the data show that ethnicity and certain values playa role in the determination of these students' affiliation to a political party. Chi-square results show that achievement, benevolence, universalism, security, tradition and conformity values are given differing importance across political parties. And, Anova results show that the tradition value has a significant mean difference across parties. Other factors such as religion and course of study are also found to have significant influence on these student's affiliation to political parties. Although 'worries' are found not to have a significant influence on student's political party affiliation, findings show that students from different political parties differ in their ratings of the different types of ' worries'. Therefore results show that ethnicity and value priorities do infl4ence these students' affiliation to a political party but ' worries' do not. The discussion section explores these findings in the context of contemporary Ugandan politics.
Keywords: Political psychology; Uganda -- Politics and government -- 1979-; Students -- Uganda -- Political activity; College students -- Uganda -- Psychology